Academic literacies of international students in New Zealand library environments. Issue 2 (1st October 2020) - Gopi, Suhasini; Tran, Ly Thi; Hutchison, Kirsten
This article is based on a study that explores international students' understanding of academic literacies in New Zealand library environments. The article aims to provide insights into international higher degree students' (IHDSs') understandings of their academic literacy practices in library environments. To address this issue, the study utilizes an interpretative framework drawing from Vygotsky's sociocultural theory. Despite a significant body of literature on international students, little is known about the interaction of this cohort with the academic library, and limited information is available on IHDSs' academic literacies in New Zealand library environments. Our article responds to this critical gap in the existing literature on international students. The findings of the study underscore the importance for librarians, learning advisors and academics to consider international students' characteristics, language proficiency, learning styles and interests in designing teaching techniques and effective support for this cohort.